2018
DOI: 10.3390/beverages4020041
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Mulberry Juice as Affected by Enzyme Treatments

Abstract: This study was conducted to investigate the effects of commercial enzymes on the extraction yield and the quality of mulberry juice. A mulberry mash was separately treated with two enzymes, namely Pectinex Ultra SP-L and Viscozyme L for different incubation times from 60 to 240 min. Determination of juice yield, total phenolic content, total anthocyanin content, antioxidant capacity, L-ascorbic acid content, total soluble solids, and titratable acidity of juice were carried out. Overall, in comparison with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
1
30
0
2
Order By: Relevance
“…A further decrease in TPC was observed after 60 min treatment which might be as a result of enzyme hydrolysis of the lateral glycosidic chains of polyphenolic compounds, resulting in less‐stable polyphenols (Butnariu et al., 2013). Generally, the increase in bioactivity upon ultrasound and enzyme treatment could be attributed to acoustic cavitation produce by ultrasound (Abid et al., 2013; Butnariu et al., 2013; Mazza et al., 2019; Nguyen & Nguyen, 2018b) and controlled enzymatic cell wall degradation (Nguyen & Nguyen, 2018a; Oszmiański et al., 2011), which facilitated the release of more soluble antioxidant polyphenols into the juice (Machado et al., 2019). Ultrasound for 30 min (US) and enzymatic treatment for 60 min were considered as the optimal time for single treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further decrease in TPC was observed after 60 min treatment which might be as a result of enzyme hydrolysis of the lateral glycosidic chains of polyphenolic compounds, resulting in less‐stable polyphenols (Butnariu et al., 2013). Generally, the increase in bioactivity upon ultrasound and enzyme treatment could be attributed to acoustic cavitation produce by ultrasound (Abid et al., 2013; Butnariu et al., 2013; Mazza et al., 2019; Nguyen & Nguyen, 2018b) and controlled enzymatic cell wall degradation (Nguyen & Nguyen, 2018a; Oszmiański et al., 2011), which facilitated the release of more soluble antioxidant polyphenols into the juice (Machado et al., 2019). Ultrasound for 30 min (US) and enzymatic treatment for 60 min were considered as the optimal time for single treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, correlation results revealed a negative relationship ( r = −0.912) between TAC and PPO activity. Enzymatic treatment has been reported to significantly increase the total anthocyanin contents in various fruit juices (Landbo & Meyer, 2004; Lee et al., 2005; Nguyen & Nguyen, 2018a; W. D. Wang et al., 2009). Overall, the results obtained in this study are comparable with previous studies on plum juice (Chun et al., 2003; Gil et al., 2002; Tomás‐Barberán et al., 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Frozen mulberries were thawed overnight at 4 • C before mashing for 60 s using a blender (Panasonic MX-GM1011GRA, Berhad, Malaysia). Mulberry must was then incubated with Pectinex Ultra SP-L (0.2% v/w) (Novozymes, Bagsvaerd, Denmark), at 50 • C for 120 min [31]. After the treatment, mulberry juice was obtained by filtration with filter papers with size pore of 20-25 µm.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Several authors have observed this phenomenon. 15,27,37 Organic acids play a relevant role in the processing of fruit juice. It serves as a mild preservative, contributes to the flavor development via a balanced sugar/acid ratio, and stimulates saliva secretion through a thirst-quenching effect.…”
Section: Effect Of Variables On Titratable Aciditymentioning
confidence: 99%